Isolation and Identification of Bacteria in Soil Samples in the Sub-Saharan Region of Sokoto, Nigeria - Yarima, Safina Abdullahi; Danjuma, Abdulrahim Muhammad (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This study investigates the isolation and identification of bacterial species in soil samples from the Gwadabawa region of Sokoto, Nigeria, focusing on their potential roles in hydrocarbon exploration and degradation. Soil samples were collected, prepared, and analyzed using microbiological methods, including serial dilution, Gram staining, and biochemical assays. The identified bacterial species include Enterococcus faecalis, Proteus mirabilis, Bacillus pumilus, Bacillus anthracis, and Kingella kingae. Among these, Enterococcus faecalis and Proteus mirabilis were the most prevalent, accounting for 29% and 28% of the isolates, respectively. These bacteria exhibit characteristics indicating hydrocarbon-rich subsurface conditions, making them valuable for exploration efforts. Factors such as soil pH and texture influence microbial activity, favoring the growth of certain bacteria. This study highlights the potential of indigenous microbial species in hydrocarbon exploration and suggests biostimulation and bioaugmentation as strategies to optimize microbial applications in exploration and bioremediation processes.